The Big Five Personality factors as Determinants of Academic Performance among undergraduates in Southwest, Nigeria (2023)
"Curriculum as the impetus for knowledge and skill acquisition occupies a central position in the school's academic activities. This study investigated the contextual determinants of effective curriculum implementation in Nigeria. The study adopted a descriptive research design of correlational type. Five hundred and forty-one (541) participants in the Southwest geopolitical zone of Nigeria, aged 37 ± 24.5 years (M = 48.41, SD = 3.75), were selected through a stratified random sampling technique. The research instrument employed was a standardized questionnaire consisting of the demographic section and measures of quality and quantity of teachers, and students; infrastructural facilities, teaching methods, and availability of appropriate and relevant teaching and learning materials for effective curriculum implementation in Nigeria. The instrument reliability coefficients are 0.76 for contextual variables and r = 0.73 for criterion variable respectively. The study answered three research questions using statistical tools like Pearson Product Moment Correlation and Regression analysis. The research questions are: (i) what is the relationship between contextual factors and effective curriculum implementation? (ii) would there be any significant joint contribution between contextual factors and effective curriculum implementation? and (iii) would there be any significant relative contribution of the contextual factors and effective curriculum implementation? The findings revealed significant relationships between the Contextual determinants (quality and quantity of teachers, quality, and quantity of students, infrastructural facilities, teaching methods, availability of relevant textbooks on relevant subjects) and Effective Curriculum Implementation indicators (availability of infrastructural facilities (r = 0.390, P < 0.05), relevant textbooks (r = 0.258, P < 0.05), method of teaching (r = 0.210, p <0.05) followed by quality of teachers ( r = 0.183, p < 0.05), followed by a number of teachers (r = 0.196, p < 0.05) followed by quality of students ( r = 0.313, p < 0.05 and finally quantity of students (r = 0.134, p < 0.05). Also, there was a significant joint contribution (R = 0.648, p < 0.05). It further revealed that 40.8% (Adj R2 = 0.408, p < 0.05) of the quality and quantity of teachers, quality and quantity of students, infrastructural facilities, teaching methods, and availability of relevant textbooks on relevant subjects to effective curriculum implementation among the participants used in Southwest geopolitical zone of Nigeria. The effective curriculum implementation was due to the prediction of the independent variables (availability of infrastructural facilities (β = 0.194, t = 3.494, p < 0.05); relevant textbooks (β = 0.109, t = 1.966, p > 0.05), teaching method (β = 0.118, t = 3.341, p < 0.05), quality of teachers (β = 0 .107, t = 2.816, p < 0.05), quantity teachers (β = 0.189, t = 2.479, p < 0.05) followed by quality of students (β = 0 .345, t = 5.948, p < 0.05) and finally followed by a quantity of students (β = 0.724, t = 3.948, p < 0.05). Based on this, it is concluded that the quality and quantity of teachers, quality and quantity of students, infrastructural facilities, teaching methods, and availability of relevant textbooks on relevant subjects are the determinants of effective curriculum implementation. Therefore, the study recommended that the government should provide the infrastructural facilities needed to enable the curriculum to be imparted easily by the teachers. Also, it recommends that trained and qualified teachers must be employed to facilitate the interpretation of the curriculum. And finally that teacher should endeavor to be student centered in interpreting the curriculum by utilizing various teaching methods to the understanding of the learners.